Combined Candida dubliniensis and Candida albicans Keratitis following a Chemical Injury. (13th May 2019) - Torosian, Justin; Mauger, Thomas
Abstract : Candida dubliniensis is an uncommon source of ocular infections and has only been reported in a single previous case of keratitis. This report documents the course of a combined Candida dubliniensis and Candida albicans keratitis following a chemical injury. Antifungal sensitivities of the two different Candida species are also demonstrated.